2014
DOI: 10.5152/eurjrheumatol.2014.140050
|View full text |Cite
|
Sign up to set email alerts
|

Articular and abarticular manifestations in type 2 diabetes mellitus

Abstract: Objective: Diabetes mellitus (DM), a worldwide high-prevalence disease, is associated with a large variety of rheumatic manifestations.It affects the connective tissues in many ways and causes alterations in the periarticular and the musculoskeletal systems. In most cases, these manifestations are associated with functional disability and pain, affecting the quality of life of the diabetic patient. The aim of our study is to review the different articular and abarticular manifestations in diabetic patients and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 17 publications
5
7
0
Order By: Relevance
“…Overall, polyneuropathy on a clinical and subclinical level was present in 39% and 56% of the patients, respectively. This is broadly consistent with a study showing that 38% of patients with T2DM and musculoskeletal disorders had polyneuropathy [ 9 ]. We do know that diabetic neuropathy increases the risk of developing adhesive capsulitis of the shoulder, a glenohumeral disorder [ 9 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Overall, polyneuropathy on a clinical and subclinical level was present in 39% and 56% of the patients, respectively. This is broadly consistent with a study showing that 38% of patients with T2DM and musculoskeletal disorders had polyneuropathy [ 9 ]. We do know that diabetic neuropathy increases the risk of developing adhesive capsulitis of the shoulder, a glenohumeral disorder [ 9 ].…”
Section: Discussionsupporting
confidence: 92%
“…This is broadly consistent with a study showing that 38% of patients with T2DM and musculoskeletal disorders had polyneuropathy [9]. We do know that diabetic neuropathy increases the risk of developing adhesive capsulitis of the shoulder, a glenohumeral disorder [9]. In our study, any form of polyneuropathy was most prevalent in patients diagnosed with a glenohumeral disorder.…”
Section: Neuropathysupporting
confidence: 92%
See 1 more Smart Citation
“…This is comparable to studies done by Cagliero et al 36 and other studies shown in the table. Flexor tenosynovitis and CTS were found to be fairly common among diabetics as shown in present study and similar findings were noted in earlier studies done by Cagliero et al 12 , Douloumpakas et al 8 and Abourazzak et al 10 The mean values of age of patients with T2DM in the various studies conducted by, Abourazzak et al 10…”
Section: Discussionsupporting
confidence: 91%
“…There is no clear definition for LJM. Some authors use the term as a synonym for stiff hand syndrome (cheiroarthropathy), whilst others use it as an umbrella term for a variety of disorders [5][6][7][8][9][10][11][12]. In this article, LJM is used as an umbrella term for specific musculoskeletal disorders of the upper extremities.…”
Section: Introductionmentioning
confidence: 99%